Лазерная абляция и фотостимулированная пассивация поверхности кристаллов Cd1–хZnхTe - Zagoruiko, Yu. A.; Kovalenko, N. O.; Khristyan, V. A.; Fedorenko, O. A.; Gerasimenko, A. S.; Dobrotvorskaya, M. V.; Mateychenko, P. V. (PE "Politekhperiodika", Book and Journal Publishers, 2011)
A new physical method of Cd1–хZnхTe-detectors passivation is proposed — the treatment of crystal surface by a laser ablation (LA) with subsequent photostimulated passivation (PhSP), during wich a high-resistance oxide layer is formed on it’s surface after the surface cleaning under intensive light irradiation effect. It is shown that the method of LA+PhSP is manufacturable and in comparison with PhSP and PhESP methods developed earlier provides a thick, homogeneous and high-oxide films, which significantly increases the surface resistivity of Cd1–хZnхTe samples and reduces leakage currents in them.